“Head of the Class”: Equity discourses related to department head appointments at one Canadian medical school - Cameron, Paula; LeBlanc, Constance; Mahalik, Anne; O'Hearn, Shawna; Simpson, Christy (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2023)
Purpose: Equitable appointments of departmental leaders in medical schools have lagged behind other Equity, Diversity, and Inclusion (EDI) advancements. The purpose of this research was to 1) analyze how policy documents communicate changing ideas of EDI, employment equity, and departmental leadership; and 2) investigate department heads’ (DH) perspectives on EDI policies and practices.Methods: We conducted a critical discourse analysis to examine underlying assumptions shaping EDI and departmental leadership in one Canadian medical school. We created and analyzed a textual archive of EDI documents (n = 17, 107 pages) and in-depth interviews with past (n = 6) and current (n = 12) DH (830 minutes; 177 pages).Results: Documents framed EDI as: a legal requirement; an aspiration; and historical reparation. In interviews, participants framed EDI as: affirmative action; relationships; numerical representation; and relinquishing privilege. We noted inconsistent definitions of equity-deserving groups.Conclusions: Change is slowly happening, with emerging awareness of white privilege, allyship, co-conspiracy, and the minority tax. However, there is more urgent work to be done. This work requires an intersectional lens. Centering the voices, and taking cues from, equity-deserving leaders and scholars, will help ensure that EDI pathways, such as those used to cultivate department leaders, are more inclusive, effective, and aligned with intentions.